The influence of drought on the occurrence of aflatoxins in maize - Kos Jovana J. (Zbornik Matice Srpske za Prirodne Nauke, 2013)
In this study, a total of 78 maize samples harvested during September and October 2012 in Vojvodina were analyzed. Presence of aflatoxins (AFs) was determined by enzyme-linked immunosorbent assay (ELISA) method. Among the 78 analyzed maize samples, even 44 (56.4%) samples were contaminated with AFs. Concentration interval between 1-10 μg/kg, 10-50 μg/kg and 50-80 μg/kg were found in 23.1%, 17.9% and 15.4% of analyzed maize samples, respectively. It was supposed that prolonged drought during spring and summer of 2012 had a great influence on high contamination frequency and concentration of AFs. [Projekat Ministarstva nauke Republike Srbije, br. III 46001]